ELECTRON MICROSCOPE STUDY OF RED CELL MEMBRANES AFTER EXPERIMENTAL INFECTION WITH THE VIRUS OF FOOT-AND-MOUTH DISEASE - Epstein, B. (The Rockefeller University Press, 1951)
Guinea pigs were inoculated with the Vallée O type strain of the virus of foot-and-mouth disease. 42 to 48 hours after inoculation red blood cells washed in saline were found to be infective for normal guinea pigs suggesting that erythrocytes carry virus entities at the height of generalization of the disease. This infection is no longer obtained at 92 hours after inoculation when general symptoms of the disease decline. A replica-transfer technique was developed with which hemolyzed blood smears could be observed under the electron microscope. By direct examination and also shadow-casting with palladium, normal red cell membranes show only a very fine structure on the surface. Rounded masses of high electron density appear in the ghosts between 24 and 72 hours after inoculation with virus. The number and particularly the density of these masses tend to increase from 24 to 42 and 72 hours. In some cases they are disposed preferentially in single lines forming ring figures; in other cases they are distributed at random. At 42 hours after inoculation it was possible to detect dense particles of 20 to 70 mµ. within the masses. Measurements of 100 masses at 72 hours gave results ranging from 116 to 437 mµ with a mean diameter of 246 mµ. Results based on 105 electron micrographs and on thousands of cells demonstrate that practically all red cell membranes contained dense masses 24 to 72 hours after inoculation. 92 hours after inoculation, coinciding with the disappearance of infectivity of the erythrocytes, the masses could no longer be seen and the membranes looked entirely normal. Although the facts reported here may be suggestive of a relationship between the dense masses within the red cell membranes and the presence of virus entities in washed erythrocytes, no definite interpretation of these findings is postulated at present.